Prenatal Exposure to Dibutyl Phthalate and Its Negative Health Effects on Offspring: In Vivo and Epidemiological Studies - Ana R. Quelhas; Melissa Mariana; Elisa Cairrao (Journal of Xenobiotics)
Dibutyl phthalate (DBP) is a low-molecular-weight phthalate commonly found in personal care products, such as perfumes, aftershaves, and nail care items, as well as in children’s toys, pharmaceuticals, and food products. It is used to improve flexibility, make polymer products soft and malleable, and as solvents and stabilizers in personal care products. Pregnancy represents a critical period during which both the mother and the developing embryo can be significantly impacted by exposure to endocrine disruptors. This article aims to elucidate the effects of prenatal exposure to DBP on the health and development of offspring, particularly on the reproductive, neurological, metabolic, renal, and digestive systems. Extensive research has examined the effects of DBP on the male reproductive system, where exposure is linked to decreased testosterone levels, reduced anogenital distance, and male infertility. In terms of the female reproductive system, DBP has been shown to elevate serum estradiol and progesterone levels, potentially compromising egg quality. Furthermore, exposure to this phthalate adversely affects neurodevelopment and is associated with obesity, metabolic disorders, and conditions such as hypospadias. These findings highlight how urgently stronger laws prohibiting the use of phthalates during pregnancy are needed to lower the risks to the fetus’s health and the child’s development.